2017
DOI: 10.1111/mec.14331
|View full text |Cite
|
Sign up to set email alerts
|

Widespread generalist clones are associated with range and niche expansion in allopolyploids of Pacific Northwest Hawthorns (Crataegus L.)

Abstract: Range and niche expansion are commonly associated with transitions to asexuality, polyploidy and hybridity (allopolyploidy) in plants. The ability of asexual polyploids to colonize novel habitats may be due to widespread generalist clones, multiple ecologically specialized clones, or may be a neutral by-product of multiple, independent origins of asexual polyploids throughout the range. We have quantified niche size and divergence for hawthorns of the Pacific Northwest using data from herbarium vouchers with k… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
57
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 38 publications
(58 citation statements)
references
References 68 publications
(142 reference statements)
1
57
0
Order By: Relevance
“…Allopolyploids that form via hybridization between two species often exhibit asexual reproduction, and are thereby triply poised to have broader environmental tolerances via reproductive assurance, greater adaptive potential due to mutations, and greater adaptive potential due to the joining of two parental genomes. Further, allopolyploids that reproduce asexually via apomictic seeds represent fixed heterozygotes, and may either behave as general-purpose genotypes with broad phenotypic plasticity and environmental tolerance, or specialized lineages that collectively confer broad tolerance to the polyploid taxon as a whole (Coughlan et al, 2017). Second, larger genome and cell sizes associated with polyploidy may lead to instantaneous shifts in physiological tolerances and trait values (Levin, 2002).…”
Section: Box 3 Ploidy and Range Sizementioning
confidence: 99%
See 2 more Smart Citations
“…Allopolyploids that form via hybridization between two species often exhibit asexual reproduction, and are thereby triply poised to have broader environmental tolerances via reproductive assurance, greater adaptive potential due to mutations, and greater adaptive potential due to the joining of two parental genomes. Further, allopolyploids that reproduce asexually via apomictic seeds represent fixed heterozygotes, and may either behave as general-purpose genotypes with broad phenotypic plasticity and environmental tolerance, or specialized lineages that collectively confer broad tolerance to the polyploid taxon as a whole (Coughlan et al, 2017). Second, larger genome and cell sizes associated with polyploidy may lead to instantaneous shifts in physiological tolerances and trait values (Levin, 2002).…”
Section: Box 3 Ploidy and Range Sizementioning
confidence: 99%
“…In the Alyssum montanum species complex, allopolyploids had higher rates of climatic niche evolution and expanded into unique climates not occupied by their diploid ancestors, while autopolyploids had slower rates of niche evolution and their niches more closely resembled those of their diploid progenitors (Arrigo et al, 2016). In hawthorns (genus Crataegus), allopolyploids had larger geographic ranges and ecological niches than diploids or autopolyploids, and this difference in range size was related to increased resource allocation to dispersal traits such as larger quantities of fruit pulp and smaller seed size trading off with reduced allocation to competitive traits (Coughlan et al, 2017(Coughlan et al, , 2014. Further, many hybrid clones occurred in several habitat types, supporting the hypothesis that polyploidization results in generalpurpose genotypes (Coughlan et al, 2017).…”
Section: Box 3 Ploidy and Range Sizementioning
confidence: 99%
See 1 more Smart Citation
“…The population-level sampling in the study demonstrated a clear contrast between diploids and tetraploids with respect to the geographic extent of their ranges. Subsequently, wider geographic distributions in allopolyploids relative to diploids were found to be correlated with greater ecological amplitude in the polyploids (Lo & al., 2013;McGoey & al., 2014;Coughlan & al., 2017). Coughlan & al.…”
Section: Introductionmentioning
confidence: 99%
“…(2014) showed that these features of the polyploids also correlated with increased relative investment in fruit biomass compared to seed biomass, suggesting a contrast between features favoring dispersal (in polyploids) versus establishment (in diploids). What we now know about hybridization in these hawthorns suggests that this contrast in fruit composition in the black-fruited taxa arose from apomixis and polyploidy having been introduced by crosses with widespread eastern North American apomictic tetraploids with much larger, red fruits (Coughlan & al., 2014(Coughlan & al., , 2017.…”
Section: Introductionmentioning
confidence: 99%